Comparative Evaluation of the Mechanical Properties and Fluoride Release of Conventional Glass Ionomer Cement and Bulk-Fill Resin Composites in Permanent Posterior Restorations in a Pakistani Population. - Riaz, Zudia; Alishba Kiran,; publication, Tahmeena Atiq; publication, Ayousha Iqbal; Haris Rehman5, Haris Rehman; publication, Muhammad Bilal (Journal of Neonatal Surgery, 2025)
Background: Dental caries is still a significant oral health issue that requires long-lasting restorative materials with good clinical outcomes and preventive advantages. For posterior restorations, bulk-fill resin composites and glass ionomer cement (GIC) are frequently utilized, each with unique benefits. Objective: Over the course of a 24-month follow-up period, assess the clinical performance, fluoride release characteristics, and survival outcomes of GIC and bulk-fill composite restorations in posterior teeth. Materials and Methods: A comparative clinical trial was conducted in two groups (n=66) on 66 posterior restorations that were allocated equally to the GIC and bulk-fill composite group (n=33 each). Restorations were also evaluated in terms of marginal integrity, surface wear, fracture resistance and secondary caries at baseline, 6, 12, 18 and 24 months using modified USPHS criteria. The fluoride release at different intervals was dialogued with the help of an ion-selective electrode. In order to determine group differences, Kaplan-Meier survival analysis and appropriate statistical tests were used. Results: Bulk-fill restorations were better than GIC in the area of marginal integrity, surface wear, color stability and survival rates (p < 0.05) at 24 months. However, the release and recharge capacity of fluoride was significantly greater at GIC during the trial period (p < 0.001). There was no significant difference in secondary caries and postoperative sensitivity between the groups. Conclusion: GIC demonstrated higher fluoride-mediated preventative effects, while bulk-fill composites offered better clinical durability. Caries-preventive potential and mechanical performance should be taken into account while choosing a material..